2021
DOI: 10.3390/ijerph18126196
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Digitization of Health Information: A Qualitative and Quantitative Study in Kenya and Lao PDR Using a Cloud-Based Maternal and Child Registration System

Abstract: Digitalization of health information can assist patient information management and improve health services even in low middle-income countries. We have implemented a mother and child health registration system in the study areas of Kenya and Lao PDR to evaluate barriers to digitalization. We conducted in-depth interviews with 20 healthcare workers (HCWs) who used the system and analyzed it qualitatively with thematic framework analysis. Quantitatively, we analyzed the quality of recorded data according to miss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In Lao PDR, there was a health screening project under the Thai Lao collaboration [ 30 ] but there were no routine services provided for Lao people. Another explanation of differences may be that the electronic health information system to support medical services in Lao PDR is still faced with difficulties [ 31 ], while Thailand has a successfully implemented electronic medical database [ 32 ]. With the limited national health insurance coverage in Lao PDR [ 6 ], most Lao diabetes patients pay out-of-pocket for the services and medications [ 7 ], while diabetes patients in Thailand do not pay for their services and medication which is covered by national health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…In Lao PDR, there was a health screening project under the Thai Lao collaboration [ 30 ] but there were no routine services provided for Lao people. Another explanation of differences may be that the electronic health information system to support medical services in Lao PDR is still faced with difficulties [ 31 ], while Thailand has a successfully implemented electronic medical database [ 32 ]. With the limited national health insurance coverage in Lao PDR [ 6 ], most Lao diabetes patients pay out-of-pocket for the services and medications [ 7 ], while diabetes patients in Thailand do not pay for their services and medication which is covered by national health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this challenge, healthcare providers in Bokeo province must have the necessary knowledge and skills to monitor and improve their performance. Additionally, they require resources and support to succeed in their efforts to improve the quality of care provided to patients (Bell & Alttahir, 2016;Chankham et al, 2017;Numair et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of a digital device to reduce maternal mortality and morbidity in low-resource settings reported that the identification and training of key champions, who were clinical staff members who received in-depth training and could support others, was the key implementation strategy enabling the feasibility of that novel intervention [ 35 ]. Other evaluation reports from India, Lao, Kenya, and Nigeria also found that staff motivation, satisfaction, confidence, and financial incentives are key factors to enable and sustain the use of novel digital health interventions [ 34 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%